The distributive impact of income taxes in Brazil - Rodrigo Cardoso Fernandes; Bernardo P. Campolina Diniz; Fernando Gaiger Silveira (International Policy Centre for Inclusive Growth (IPC-IG), 2018)
Brazil has always been known as a country marked by inequality. Whether of opportunities, income or property, this inequality is manifest in all stages of wealth accumulation. Within this dire landscape, the country has always stood alongside much poorer nations, while countries with similar income and development profiles have presented substantially better indicators. Many scholars and academics have addressed this disturbing national quirk, analysing its origins and the main variables that have determined its persistent dynamics within Brazilian society. One element that has garnered relatively less attention in the analysis of the determinants of inequality is how the organisation of the tax system can impact the distribution of income. Therefore, in light of our investigation, one of the issues that has been identified as reinforcing the social injustices in Brazil is its national tax structure. [...]
Keywords: 330; taxation and inequality; tax progressivity; income concentration in Brazil; Pareto interpolation